Learning and language with a neuroscientist- pedagogical approach development and acquisition of a second language - Segovia Rubio, Rosa Del Carmen (2018)
The neuroscientist advances and developments help us to  comprehend the brain function and how can we take advantage of these advances for the benefit of a specific area. Learning and language has a physiological and cognitive explanation. Both explanations are considered for the neuroscience andthe neuropedagogical. How, when and why do we learn are questions that have a response in the light of the neuroscience. The acquisition of language is done in a natural manner without forgetting the brain complex process. The acquisition of a second language benefits to the brain and provides it with new neural nets.